A mediated moderation model of haptic exposure duration and valuation of an item - Jenita, Esti (2013)
Past research on haptic exposure done in the area of marketing have shown that increased duration of time given for touch increases product’s monetary valuation, and that individuals have different levels of Need For Touch (NFT). This research aims to test if the positive relationship between duration of haptic exposure and valuation of an item differ for all consumers, at different NFT levels. A mediated moderation study was carried out with NFT as the moderator and the respondent’s perceived ownership of the product as the mediator. Results showed that a longer duration of haptic exposure to products leads to a significant increase in monetary valuation by high NFT individuals. However, the same increase in duration of exposure did not result in a significant increase in monetary valuation of products for low NFT individuals. The authors then discussed the managerial implications for traditional retailers and online retailers.